Components of interprofessional education programs in neonatal medicine: A focused BEME review: BEME Guide No. 73. (3rd August 2022) - Parmekar, S.; Shah, R.; Gokulakrishnan, G.; Gowda, S.; Castillo, D.; Iniguez, S.; Gallegos, J.; Sisson, A.; Thammasitboon, S.; Pammi, M.
Abstract: Background: Care delivery in neonatology is dependent on an interprofessional team. Collaborative learning and education amongst professionals can lead to successful management of critically ill patients. This focused BEME review synthesized the components, outcomes, and impact of such interprofessional education (IPE) programs in neonatal medicine. Methods: The authors systematically searched four online databases and hand-searched MedEdPublish up to 10 September 2020. Two authors independently screened titles, abstracts, full-texts, performed data extraction and risk of bias assessment related to study methodology and reporting. Discrepancies were resolved by a third author. We reported our findings based on BEME guidance and the STORIES (STructured apprOach to the Reporting in health education of Evidence Synthesis) statement. Results: We included 17 studies on IPE in neonatal medicine. Most studies were from North America with varying learners, objectives, instruction, and observed outcomes. Learners represented nurses, respiratory therapists, neonatal nurse practitioners, patient care technicians, parents, early interventionists, physicians, and medical trainees amongst others. Risk of bias assessment in reporting revealed poor reporting of resources and instructor training. Bias assessment for study methodology noted moderate quality evidence with validity evidence as the weakest domain. IPE instruction strategies included simulation with debriefing, didactics, and online instruction. Most studies reported level 1 Kirkpatrick outcomes (76%) and few reported level 3 or 4 outcomes (23%). Challenges include buy-in from leadership and the negative influence of hierarchy amongst learners. Conclusions: This review highlights IPE program components within neonatal medicine and exemplary practices including a multimodal instructional approach, asynchronous instruction, an emphasis on teamwork, and elimination of hierarchy amongst learners. We identified a lack of reporting on program development and instructor training. Future work should address long term knowledge and skill retention and impact on patient outcomes and organizations.